PENGARUH E-BANKING, KUALITAS PELAYANAN, KUALITAS KOMUNIKASI, TERHADAP KEPERCAYAAN MELALUI LOYALITAS NASABAH PADA PT BCA KCP PANTAI INDAH KAPUK JAKARTA BARAT - Rosiana, Nindya (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2018)
The purpose of this study is to fing out how much influence e-banking, the quality of service,the quality of communication, trust, of customer loyalty at PT. Bank Central Asia Subbranch OfficePantai Indah Kapuk Jakarta. The type of this research is survey. This research data was collectedfrom 125 customers of PT. Bank Central Asia Subbranch Office Pantai Indah Kapuk Jakarta questionwere given by using quetionnaires which consist of closed question. Respondent's answers to closedquestion about the variables studied in this study then in the analysis of Structural EquationModelling using AMOS 6.00 program. From the results of research shows that the e-banking variable(X ) has no significant effect on trust (Z). Variable of service quality (X ) have significant effect on 1 2trust (Z). The communication quality variable (X ) has no significant effect on trust (Z). The e- 3banking variable (X ) has no significant effect on customer loyality (Y). The communication quality 1variable (X ) has no significant effect on customer loyality (Y). The e-banking variable (X ) has no 3 1significant effect on service quality (X ). The service quality variable (X ) have significant effect on 2 2communication quality (X )